Visual influence on human locomotion Modulation to changes in optic flow: Modulation to changes in optic flow - Prokop, T.; Schubert, M.; Berger, W. (Experimental brain research, 1997)
The effect of an optic flow pattern on human locomotion was studied in subjects walking on a self-driven treadmill. During walking an optic flow pattern was presented, which gave subjects the illusion of walking in a tunnel. Visual stimulation was achieved by a closed-loop system in which optic flow and treadmill velocity were automatically adjusted to the intended walking velocity (WV). Subjects were instructed to keep their WV constant. The presented optic flow velocity was sinusoidally varied relative to the WV with a cycle period of 2 min. The independent variable was the relative optic flow (rOF), ranging from -1, i.e., forward flow of equal velocity as the WV, and 3, i.e., backward flow 3 times faster than WV. All subjects were affected by rOF in a similar way. The results showed, firstly, an increase in stride-cycle variability that suggests a larger instability of the walking pattern than in treadmill walking without optic flow; and, secondly, a significant modulating effect of rOF on the self-chosen WV. Backward flow resulted in a decrease, whereas forward flow induced an increase of WV. Within the analyzed range, a linear relationship was found between rOF and WV. Thirdly, WV-related modulations in stride length (SL) and stride frequency (SF) were different from normal walking: whereas in the latter a change in WV is characterized by a stable linear relationship between SL and SF (i.e., an approximately constant SL to SF ratio), optic flow-induced changes in WV are closely related to a modulation of SL (i.e., a change of SL-SF ratio). Fourthly, this effect of rOF diminished by about 45% over the entire walking distance of 800 m. The results suggest that the adjustment of WV is the result of a summation of visual and leg-proprioceptive velocity informations. Visual information about ego-motion leads to an unintentional modulation of WV by affecting specifically the relationship between SL and SF. It is hypothesized that the space-related parameter (SL) is influenced by visually perceived motion information, whereas the temporal parameter (SF) remains stable. The adaptation over the entire walking distance suggests that a shift from visual to leg-proprioceptive control takes place.